A Comparative Study to Evaluate the Effectiveness between Synergic Activities of 0.1% Polyhexanide and Rigenase® (Fitostimoline® Plus spray) versus a Hydrating Formulation for the Topical Management of Rubbing Injuries Secondary to Atopic Dermatitis - Di Brizzi, Eugenia Veronica; Balato, Anna; Caccavale, Stefano; Lupoli, Amalia; Panetti, Carlo; Argenziano, Giuseppe (Dermatology Practical & Conceptual, 2025)
Introduction: Managing rubbing injuries in atopic dermatitis is challenging and has a significant impact on patients' quality of life. Polyhexamethylene biguanide (PHMB) and Rigenase® (a patented Triticum vulgare extract) show promise in tissue repair and antimicrobial activity.Objective: The aim of this study was to compare the effectiveness of two topical treatments, Fitostimoline® Plus spray and a hydrating formulation with hyaluronic acid, in rubbing injuries secondary to atopic dermatitis.Materials and Methods: This comparative study enrolled 68 patients with atopic dermatitis and rubbing injuries, randomly assigned to Group A (N=38) receiving Fitostimoline® Plus spray (0.1% PHMB and Rigenase®) or Group B (N=30) receiving a hyaluronic acid spray. The primary endpoint was the clinical lesion response at 10 days post-treatment. Secondary endpoints included pain reduction (Visual Analogue Scale, VAS) and patient satisfaction (Dermatology Life Quality Index,DLQI).Results: Group A had a significantly higher complete response rate (81.3% vs. 64.3%, P <0.001). Partial response rates were also higher in Group A (P = 0.045). Pain reduction was greater in Group A (VAS: 6.8 ± 1.2 to 2.4 ± 0.8) compared to Group B (7.1 ± 1.3 to 3.9 ± 1.0) (P <0.001). DLQI scores improved more in Group A (12.5 ± 3.5 to 3.2 ± 1.1) than in Group B (13.0 ± 3.2 to 6.5 ± 1.4) (P <0.001). Dermoscopic examinations showed significant skin barrier improvement in Group A (P <0.001).Conclusion: Fitostimoline® Plus spray, with 0.1% PHMB and Rigenase®, offers superior treatment for chronic lesions in atopic dermatitis, enhancing wound healing and patient quality of life.